SAID NURSI ISLAMIC EDUCATION APPROACH - Paizaluddin Baihaqy; Imam Nasruddin; Sandra Susanto (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
The approach to Islamic education implemented by Said Nursi is still relevant to be applied in the current condition of Islamic education. This paper explores the works of Said Nursi, especially those summarized in Risalah E Nur. This research focuses on the scope of Islamic education approaches, with the main problem being how Said Nursi applies the approaches of Islamic education in educational institutions, community forums, and Risale-i Nur. This study uses qualitative data in the form of literature and verbal information. It uses analytical descriptive analysis techniques, which analyze and conclude from confirmed opinions, and content analysis, which analyzes the meaning of assumptions, ideas, or statements to gain understanding and conclusion after being identified that the approaches in the application of the educational process carried out by Said Nursi, among others: psychological approach, sociocultural approach, religious approach, historical approach, comparative approach, philosophical approach. The psychological, sociocultural, religious, historical, comparative, and philosophical approaches remain 'oriented towards 'seeking the truth' and 'appreciating differences,' not 'seeking victory' and 'hating differences and claiming the proper self. This method and approach will widen the horizons between teachers, students, teacher-students, and teacher participants in education-community; as a lively educational interaction. Education now really needs such a healthy (climate) situation.